Clinical Value of Fecal Calprotectin in Predicting Mucosal Healing in Patients With Ulcerative Colitis - Chen, Fang; Hu, Yue; Fan, Yi-Hong; Lv, Bin (Frontiers in Medicine, 2021)
AIM: This is study aimed to evaluate the clinical significance of Fecal Calprotectin(FC) in assessment of ulcerative colitis (UC) patients’ endoscopic patterns and clinical manifestation. METHODS: A total of 143 UC patients who received colonoscopy and 108 controls were included. After providing stool samples, patients underwent total colonoscopy. FC was measured by enzyme-linked immunosorbent assay (ELISA). Clinical activity was based on the Mayo score. Endoscopic findings was scored by the Ulcerative Colitis Endoscopic Index of Severity (UCEIS). Correlation analysis and Receiver-Operator Characteristic (ROC) analysis were carried out to determine the significance of measurements. RESULTS: The median (interquartile range, IQR) of FC levels were 211(43-990) μg/g in UC and 87.5(40.50~181) μg/g in the control group. Fecal calprotectin correlated significantly with both Mayo and UCEIS scores (Spearman’s r 0.670 and 0.592, P<0.01). With a cut-off value of 164 μg/g for fecal calprotectin concentration, the area under the curve (AUC) in receiver operator characteristic analysis was 0.830, sensitivity 85.42%, specificity 73.68%, positive predictive value (PPV) 62.12%, and negative predictive value (NPV) 9.10% in predicting clinical active disease. Similarly, the power of FC to predict mucosal healing (MH) was modest. With a cut-off value of 154.5 μg/g, the AUC was 0.839, sensitivity 72.34% and specificity 85.71%. CONCLUSION: For evaluating the disease activity of UC, FC is a clinically relevant biomarker for both clinical active disease and MH in patients with UC. But the cut-off value still need large and multicenter studies.